Microsatellite markers for the Triticum timopheevi-derived leaf rust resistance gene Lr18 on wheat 5BL chromosome - Sadeghabad, Ali Aliakbari (Breeding science, 2017)
Leaf rust, caused by Puccinia triticina, is a common wheat disease worldwide. Developing resistant cultivars through deploying new or pyramiding resistance genes in a suitable line, is the most effective approach to control this disease. However, to stack genes in a genotype, efficient and reliable markers are required. In the present study, F2 plants and their corresponding F3 families from a cross between the resistant line; Thatcher (Tc) Lr18, and the susceptible cultivar 'Boolani' were used to map rust resistance gene, Lr18 using SSR markers on chromosome 5BL of hexaploid wheat. The P. triticina pathotype no 15 was used to inoculate plants. Out of 20 primers tested, eight showed polymorphism between the two parents and were subsequently genotyped in the entire F2 population. The markers Xgpw7425 and Xwmc75 flanked the locus at a distance of 0.3 and 1.2 cM, respectively. Analysis of 81 genotypes from different backgrounds with these two markers confirmed their usefulness in screening absence or presence of Lr18. Therefore, these markers can be used for gene postulation and marker-assisted selection (MAS) of this gene in wheat breeding programs in future